Pengembangan Modul Ajar Pendidikan Pancasila Untuk Meningkatkan Minat Belajar Kelas V SD Negeri 1 Kujon Tahun Pelajaran 2023/2024 - Titin Sulistyowati; Sri Suwartini; Isna Rahmawati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The aim of this research is to determine the feasibility of the Pancasila Education teaching module, determine students' responses to the implementation of the Pancasila Education teaching module, determine students' interest in learning after implementing the Pancasila Education teaching module, and determine the development of the Pancasila Education teaching module in the material of Chapter 3 Cultural Diversity. My Indonesia Topic B Let's Preserve Indonesian Culture. This type of research is Development Research (Research and Development) using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The sample in this research was 18 class V students at SD Negeri 1 Kujon. The data collection techniques used were interviews, observation, questionnaires, tests and documentation. The results of this research show that the development of the Pancasila Education teaching module can increase the learning interest of class V students at SD Negeri 1 Kujon with a percentage increase of 52%.